2012
DOI: 10.1002/wsb.129
|View full text |Cite
|
Sign up to set email alerts
|

Managing nesting by Chihuahuan ravens on H‐frame electric transmission structures

Abstract: Electric utility structures occur widely in natural and human-dominated landscapes and are often used by birds for nesting. Nests can cause power outages, fires, and electrocution of birds and their young, particularly if nests occur directly above energized equipment and incorporate metal wire. Chihuahuan raven (Corvus cryptoleucus) nests often contain metal wire and occur over energized equipment. To explore a proactive risk mitigation strategy we deployed novel nest diverters on 51 structures supporting a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Whereas Dwyer and Leiker (2012) demonstrated that nest deterrents were successful across a single breeding season for preventing nesting by Chihuahuan ravens, we were able to prevent the ravens from nesting over 2 additional breeding seasons. In addition, we were able to prevent nesting over the center phase of H-frame transmission structures on a line segment 17.7 times as long as the treated segments used by Dwyer and Leiker (2012). However, apparently in response to nest deterrents, Chihuahuan ravens successfully shifted nesting to corner structures, and for the first time in the recorded history of this line (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), to outer phases and to overhead-shield-wire attachment brackets.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Whereas Dwyer and Leiker (2012) demonstrated that nest deterrents were successful across a single breeding season for preventing nesting by Chihuahuan ravens, we were able to prevent the ravens from nesting over 2 additional breeding seasons. In addition, we were able to prevent nesting over the center phase of H-frame transmission structures on a line segment 17.7 times as long as the treated segments used by Dwyer and Leiker (2012). However, apparently in response to nest deterrents, Chihuahuan ravens successfully shifted nesting to corner structures, and for the first time in the recorded history of this line (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), to outer phases and to overhead-shield-wire attachment brackets.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also supported our 3 predictions that there would be fewer nests on structures with deterrents (treated structures), that nests would not occur over the center phase on treated structures, and that Chihuahuan ravens would perch on overhead shield wires. Whereas Dwyer and Leiker (2012) demonstrated that nest deterrents were successful across a single breeding season for preventing nesting by Chihuahuan ravens, we were able to prevent the ravens from nesting over 2 additional breeding seasons. In addition, we were able to prevent nesting over the center phase of H-frame transmission structures on a line segment 17.7 times as long as the treated segments used by Dwyer and Leiker (2012).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The design parameters of our UAV also make it ideal for conducting close evaluations of overhead power line structures (Lobermeier et al 2012). These structures require regular surveys to evaluate potential operational and maintenance concerns before these concerns develop into unplanned emergencies (Li and Ruan 2010;Dwyer and Leiker 2012). However, improvements to our design to reduce weight and improve durability are needed prior to practical widespread use.…”
Section: Discussionmentioning
confidence: 99%